Thermal response of a packaged narrowband optical filter based on biconically tapered depressed-cladding fibre - Guerra, C. P.; Malheiros-Silveira, G. N. [UNESP]; Celaschi, S. (My University, 2019)
The thermal response of packaged biconic taper filter with a free spectral range of 1.7 nm is investigated over a temperature range of 0–70°C. The filter length dependence with temperature is estimated from the spectral offset. This device presented thermal stability of 3 × 10−3 nm/°C, measured at λ0 = 1550 nm.